2016
DOI: 10.1109/jproc.2016.2543266
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Detection of GNSS Jammers on Consumer Grade Satellite Navigation Receivers

Abstract: | Jamming is the act of intentionally directing powerful electromagnetic waves toward a victim receiver with the ultimate goal of denying its operations. This paper describes the main types of Global Navigation Satellite System (GNSS) jammers and reviews their impact on GNSS receivers. A survey of state-of-the-art methods for jamming detection is also provided. Different detection approaches are investigated with respect to the receiver stage where they can be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 124 publications
(63 citation statements)
references
References 21 publications
(36 reference statements)
0
54
0
3
Order By: Relevance
“…The use of hardware-simulated GNSS data collected in the presence of jamming was considered more realistic and appropriate than Monte Carlo simulations for demonstrating the effectiveness of RTD processing. In the simulations, baseband GPS L1 coarse aquisition (C/A) signal samples were generated according to (2) with BB [n] modeled as AWGN. The simulation parameters used for the computa- Abbreviations: C/A, coarse aquisition; SNR, signal-to-noise power ratio.…”
Section: Validation Through Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of hardware-simulated GNSS data collected in the presence of jamming was considered more realistic and appropriate than Monte Carlo simulations for demonstrating the effectiveness of RTD processing. In the simulations, baseband GPS L1 coarse aquisition (C/A) signal samples were generated according to (2) with BB [n] modeled as AWGN. The simulation parameters used for the computa- Abbreviations: C/A, coarse aquisition; SNR, signal-to-noise power ratio.…”
Section: Validation Through Simulationsmentioning
confidence: 99%
“…1 Radio frequency (RF) interference, in particular, can significantly reduce the performance of a GNSS receiver and, in certain cases, completely deny GNSS signal reception. 2 RF interference generally consists of an unwanted signal component at the receiver antenna. This component can overpower the weak GNSS signals reducing or preventing GNSS receiver operations.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that, for the acquisition, the probability of detection and the probability of false alarm are vulnerable to the presence of interference, and that, for the tracking, the carrier-to-noise density ratio (C/N 0 ) decreases and the variance of the position solution increases. In addition to C/N 0 , other observables available at different stages of the receiver processing chain are affected by the jammer signal (Borio et al 2016). For example, the automatic gain control (AGC) level drops in response to increased power in the GNSS band, and the running delay lock loop (DLL) variance and the running phase lock loop (PLL) variance increase due to the rise in the noise level (Bhuiyan et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent advances in global navigation satellite system (GNSS) technology, jamming, blockage and severe multipath fading can still significantly impair the performance of receivers or completely deny GNSS positions and time services. Interference can impact the front end, acquisition, tracking and position stages of a receiver (Borio et al 2016). Even a low-power jamming signal can potentially jeopardize the functionality of receivers in a circular region around the jammer with a radius of several kilometers.…”
Section: Introductionmentioning
confidence: 99%